2021
DOI: 10.3390/healthcare10010019
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Behavior at Hospitals and Factors Associated to Safer Care: A Systematic Review

Abstract: Disruptive behavior creates a dysfunctional culture that has a negative impact on work relations and influences the quality of care and safety of the patient. The objective of the present work is to provide the best methodological quality scientific evidence available on disruptive behavior at a hospital, the aspect associated with the safety of the patient, and its impact on quality of care. For this, we included studies that addressed the prevalence of disruptive behaviors observed in the area of hospital he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…On the other hand, some studies put forward the evaluation framework of hospital resilience from the perspective of hospital management, (Chen et al, 2021 ; Shirali et al, 2016 ; Tharanga & Fernando, 2021 ) such as evaluating the relevant indicators in the four dimensions of technology, organization, society and economy, and considering two types of costs related to hospital resilience: (1) systematic impact of disruption which shows the differences of performance index before and after disasters, and (2) total recovery effort which indicates the costs of recovery action that would be done after disruptions to return the system state to pre-disruption one. (Renzetti & Mango, 2020 ; Moreno-Leal et al, 2021 ; Pacheco, Martimbianco, Roitberg, et al, 2021 ) Shuang Zhong,(Zhong et al, 2015 ) based on the modified Delphi, proves that equipment for on-site rescue, plan initiation, equipment for referral of patients with complex care needs are crucial indicators of a comprehensive framework of hospital resilience. Meanwhile, the individual resilience of hospital staff also is considered as an influencing factor of hospital resilience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, some studies put forward the evaluation framework of hospital resilience from the perspective of hospital management, (Chen et al, 2021 ; Shirali et al, 2016 ; Tharanga & Fernando, 2021 ) such as evaluating the relevant indicators in the four dimensions of technology, organization, society and economy, and considering two types of costs related to hospital resilience: (1) systematic impact of disruption which shows the differences of performance index before and after disasters, and (2) total recovery effort which indicates the costs of recovery action that would be done after disruptions to return the system state to pre-disruption one. (Renzetti & Mango, 2020 ; Moreno-Leal et al, 2021 ; Pacheco, Martimbianco, Roitberg, et al, 2021 ) Shuang Zhong,(Zhong et al, 2015 ) based on the modified Delphi, proves that equipment for on-site rescue, plan initiation, equipment for referral of patients with complex care needs are crucial indicators of a comprehensive framework of hospital resilience. Meanwhile, the individual resilience of hospital staff also is considered as an influencing factor of hospital resilience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A systematic review has recently been carried out to provide the best methodological quality scientific evidence available on disruptive behavior at a hospital, the aspect associated with the safety of the patient, and its impact on quality of care [ 12 ]. Of the studies identified in the systematic review, many measured disruptive behaviors in specific samples of professional groups such as physicians [ 13 ] or nurses [ 14 , 15 ], in specific clinical areas such as the surgical setting [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The negative consequences of disruptive behaviours (DBs) involving healthcare workers have been shown to threaten the institution's image, staff morale, finances, and patient safety [1] . Therefore, hospital managers need to address this matter early to ensure the pursuit of the hospital's mission and to establish confidence in the facility's operational and business activities and goals.…”
Section: Introductionmentioning
confidence: 99%
“…More research is required to investigate the problem of DBs in radiography as society is increasingly becoming violent, with a global upsurge in the level of aggression in the workplace [13] . Disruptive behaviours are a major concern for radiographers as they may compromise patient safety [1] . Patient safety is at the centre of all radiographers do [17] .…”
Section: Introductionmentioning
confidence: 99%